PERAN QRIS DALAM MENDORONG PERTUMBUHAN PENDAPATAN PELAKU UMKM DI INDONESIA - Vina Nailatul Izza; Rafli Achmad Alamsyah (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2026)
Digital transformation in payment systems has become an important element in the development of the Micro, Small, and Medium Enterprises (MSME) sector in Indonesia. One of the innovations developed to promote transaction efficiency and financial inclusion is the Quick Response Code Indonesian Standard (QRIS), which was introduced by Bank Indonesia in 2019. This study aims to describe and understand the role of QRIS in driving the income growth of MSME players in Indonesia through a descriptive qualitative approach. Data collection was carried out using documentary studies through various official sources such as publications from Bank Indonesia, the Financial Services Authority (OJK), the Central Statistics Agency (BPS), reports from the Ministry of Cooperatives and MSMEs, and relevant academic literature. This study focuses on exploring the contribution of QRIS to transaction convenience, market access, and opportunities for increasing MSME income as part of the development of the digital economy in Indonesia.